International student-migrant flows and growth in low- and middle-income countries: brain gain or brain drain?. Issue 34 (21st July 2021) - Rasamoelison, Jean Donovan; Averett, Susan; Stifel, David
ABSTRACT: The number of students flowing from low-income countries to high-income countries has grown over the past several decades but is likely to fall substantially in the coming years due to the coronavirus pandemic. To gauge the potential impact of the coronavirus-induced reduction in the international flow of student migrants, we estimate the pre-pandemic effects of student migration from 122 low- and middle-income countries to French- and English-speaking high-income countries on the economic growth of the sending countries. Using region fixed-effects and instrumental-variables estimators to address the potential endogeneity of student-migrant flows, we find positive and statistically significant effects of student migration on per capita GDP in sending countries. These findings are robust to different time lags, and are increasing over time. Our results indicate that student migrants have a modest but meaningful impact on the short-run economic growth of their home countries. In terms of the mechanisms through which student-migrant flows can affect growth of the home countries, we find evidence of 'incentive effects' for students going to English-speaking countries, and evidence of student-migrant flows affecting interest in politics and democratic political systems in the sending countries.